Evaluation of the quality of soybean seed produced in Paraná - Costa, Nilton P. da; França Neto, José de B.; Pereira, Luiz A. G.; Henning, Ademir A. (Pesquisa Agropecuaria Brasileira, 2014)
This study was carried out to determine the factors reducing the quality of soybean (Glycine max (L.) Merrill) seeds produced in the state of Paraná, Brazil. The cultivars studied were 'Paraná', 'Davis' and 'Bossier'. The three major soybean producing areas of the State were surveyed in 1979/80, 1981/82 and 1982/83. A total of 1,661 seed samples were analysed. The evaluations were standard germination, tetrazolium test (to estimate field deterioration, mechanical damage and stink bug attack) and varietal purity. The State was divided into three regions based upon the average temperature (ta) of February: T1 region =ta > 24ºC. T2 = ta between 22 and 24ºC and T3 = ta < 22ºC. The results showed 'Paraná' having the best seed quality followed by 'Bossier' and 'Davis'. The most favorable region for seed production was the region T3. However, in this region during 1982/83, 'Bossier' presented low seed quality due to excessive rains during the seed maturation period. Regarding to varietal purity, 'Paraná' was superior to the other two. 'Bossier' had higher number of seed lots discarded, specially in the agricultural years of 1979/80 and 1981/82.
Keywords: Glycine max; deterioration; varietal purity.